Diseño y construcción de un banco de pruebas de presión, mecánicas y termodinámicas para turbocompresor de geometría fija T20 250-300 R 4947 con fines didácticos. - Moreno Castro, Darwin Alberto; Ángel Peñuela, Mario Sneider (Universidad Antonio Nariño, 2023)
This project shows the design and construction of the turbo compression system test bench to be used in the laboratory, in order to reinforce the topics seen during the course of the curricular project such as thermodynamics, fluid mechanics and thermal machines of the FIMEB of the Antonio Nariño University